Do emotional carryover effects carry over? - Nikhil Masters; Tim A. Lloyd; Chris Starmer (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2024)
Existing research has demonstrated carryover effects whereby emotions generated in one context influence decisions in other, unrelated ones. We examine the carryover effect in relation to valuations of risky and ambiguous lotteries with a novel focus on the comparison of carryovers arising from a targeted stimulus (designed to elicit a specific emotion) with those arising from a naturalistic stimulus (designed to produce a more complex emotional response). We find carryover effects using both types of stimuli, but they are stronger for the naturalistic stimulus and in the context of ambiguity, providing a proof of concept that carryover effects can be observed when moving away from highly stylised settings. These effects are also gender specific with only males being susceptible. To probe the emotional foundations of the carryover effect, we conduct analysis relating individual self-reports of emotions to valuation behaviour. Our results cast doubt on some previously claimed links between specific incidental emotions and risk taking.
Keywords: C91; D81; D91; 330; Incidental emotions; emotional carryover; Risk; Ambiguity; Naturalistic